The Role of IgG4 in Autoimmunity and Rheumatic Diseases - Maslinska, Maria; Dmowska-Chalaba, Joanna; Jakubaszek, Michal (Frontiers in Immunology, 2022)
The distinguishing of the IgG4-related disease (IgG4-RD) from among other rheumatic diseases has brought attention to the IgG4 subclass of immunoglobulins. It is the least numerous subclass among immunoglobulins G. In general, IgG4 is considered to be non-inflammatory and tolerance inducing, due to its unique structure. However, in IgG4-RD this antibody plays a pathogenic role in activation of the fibrinogenesis and of the inflammatory process; there are also suggestions that it may be a marker of an abnormal inflammatory response. The importance of IgG4 for the pathogenesis of allergic diseases, with a vital role of its ratio to immunoglobulin E (IgE/IgG4 ratio), has been known for years. The role of IgG4 in the course and pathogenesis of rheumatic diseases is still being researched and is not yet fully understood. Increased IgG4 levels have been revealed in rheumatoid arthritis, although no clear link between this phenomenon and disease activity has been demonstrated. There are articles on the potential importance of IgG4 concentration (of both elevated and decreased serum levels) in Sjogren’s syndrome. Additionally, anti-nuclear IgG4 antibody significant titers have been detected in SLE patients, and it has been suggested that the effect of these antibodies on complement consumption and the production of proinflammatory cytokines may play a role in inhibiting the progression of SLE. IgG4 plays a role in autoimmune diseases other than rheumatic diseases, such as pemphigus, bullous pemphigoid, idiopathic membranous glomerulonephritis, or myasthenia gravis, but also in helmints infections. Research shows the importance of IgG4 in malignancy of neoplasms. Melanoma cells are known to stimulate IgG4 production through a modified Th2-based inflammatory response. The role of this immunoglobulin in cholangiocarcinoma is also considered as possible. The aim of this review article is to discuss the current knowledge of IgG4 not only from the perspective of the IgG4-RD but also from a point of view of other autoimmune diseases with particular emphasis on rheumatic diseases.